Use of lectin as a vector molecule for delivery of medicinal products to cells and tissues - Antonyuk, V.O.; Klyuchivska, O.Yu.; Antonyuk, R.V.; Lozynskyi, A.V.; Pohranychna, Kh.R.; Lesyk, R.B.; Stoika, R.S. (Вiopolymers and Cell, 2016)
Aim. The conjugation of low-molecular compounds with antitumor activity to lectin and evaluation of the biological activity of the obtained conjugate. Methods. Organic synthesis; obtaining and analyzing Pisum sativum agglutinin with thiopyrano[2,3-d]thiazole derivative conjugate; its biological testing on cell cultures and histological samples. Results. A conjugate of the Pisum sativum lectin with the thiopyrano[2,3-d]thiazole derivative was obtained. Conjugation was carried out through the interaction of the aldehyde groups with the amino groups of lectin in the alkaline medium (pH 9.0). The compound (0.4 mg) was immobilized on lectin (10 mg). Conjugation of pea lectin with the antineoplastic agent led to a ~ 2.5-fold increase in the inhibitory effect tested on a L1210 mouse leukemia cells line. The antineoplastic effect of the studied conjugate is fully manifested only on the third day after the beginning of experiment, possibly after penetration of the conjugate into cells and its desintegration. Conclusions. The results may be used for development of new drug delivery systems.